Hidrosefalus Komunikans akibat Perdarahan Subaraknoid: Sebuah Laporan Kasus - Fitriyani, Fitriyani; Adila, Naza Tsasbita Hayuning (CV. Jasa Sukses Abadi, 2024)
Hydrocephalus is one of the most common sequelae after subarachnoid hemorrhage, and is a major cause of high morbidity and mortality from this disease. Changes in cerebrospinal fluid (CSF) dynamics, obstruction of arachnoid granulations by blood products, and adhesions in the ventricular system are some of the mechanisms by which hydrocephalus occurs after subarachnoid hemorrhage. Inflammation, apoptosis, autophagy, and oxidative stress are important causes of hydrocephalus. Transforming growth factors, matrix metalloproteinases, and iron ultimately cause fibrosis and blockage. Surgery is the most common and efficient therapy, although there are risks from different surgical methods, including lamina terminalis fenestration, ventricle-peritoneal shunting, and lumbar-peritoneal shunting. Case report of a 46 year old male patient. A 46 year old man with severe cephalgia that comes and goes and interferes with activities throughout the head such as being pricked since 2 weeks of before coming to hospital. Other complaints of vomiting spraying, slightly black color 6x, fainting 2x for <15 minutes. Physical examination revealed stiff neck and Kernig's sign. CT scan showed subarachnoid hemorrhage filling the interhemispheric fissure, bilateral frontal cortical sulci, left temporal, suprasellar cisterna and Hydrocephalus communicans. In addition, hyponatremia was found, (133 mmol/L).